PECULIARITIES OF THE MODEL OF ETHNOCULTURAL TOURISM OF UZBEKISTAN - Rustamkulovna, Safarova Tumaris (International Journal of Psychosocial Rehabilitation, 2020)
The model of ethnocultural tourism in Uzbekistan is rich in historical, cultural and ethnographic facts. This article summarizes international and national experiences in building a model of ethnocultural tourism in Uzbekistan, analyzes their social and philosophical nature, and elaborates on the laws of tourism development in the country and the practical recommendations for it.